History of the Wars, Books I and II: The Persian War - Procopius; Dewing, H. B. (Henry Bronson), 1882-1956 (Salt Lake City, UT : Project Gutenberg, 2005)
"History of the Wars, Books I and II: The Persian War" by Procopius is a historical account written in the early 6th century. This work details the military campaigns of the Byzantine Emperor Justinian against various enemies, particularly focusing on the wars against the Persians. Procopius, who was a contemporary of these events and served as an adviser to the general Belisarius, provides first-hand insights into the strategies and outcomes of these significant conflicts. The opening of this historical narrative establishes Procopius's credentials as a historian with a unique perspective on the events he recounts. He emphasizes the importance of documenting these wars$1 (Bnot merely for the sake of history, but as a resource for future generations engaged in similar struggles. In the initial sections, Procopius outlines the context of Roman-Persian relations, highlighting key historical figures such as the Emperor Theodosius, and introduces notable battles and political maneuvers throughout various conflicts. The text begins detailing the complexities of these interactions and lays the groundwork for a more in-depth exploration of the wars that will follow in subsequent chapters. (This is an automatically generated summary.)s
Release date is 2005-09-27
E-text prepared by Jonathan Ingram, jayam, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Iran -- History -- To 640; Vandals; Goths -- Italy; Byzantine Empire -- History -- Justinian I, 527-565; Justinian I, Emperor of the East, 483?-565